2021
DOI: 10.5194/essd-2020-323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long term variations of actual evapotranspiration over the Tibetan Plateau

Abstract: Abstract. Terrestrial actual evapotranspiration (ETa) is a key parameter controlling the land-atmosphere interaction processes and the water cycle. However, the spatial distribution and temporal changes of ETa over the Tibetan Plateau (TP) remain very uncertain. Here we estimate the multiyear (2001–2018) monthly ETa and its spatial distribution on the TP by a combination of meteorological data and satellite products. Validation against data from six eddy-covariance monitoring sites yielded a root mean square e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…In this study, we developed a 37-year monthly ET dataset with a 0.01° spatial resolution for the 415 TP using the newly developed MOD16-STM model coupled with soil information to investigate the spatial distribution and temporal trends of the ET on the TP. Although previous studies have been conducted on the ET climatology on the TP (Peng et al, 2016;Wang et al, 2018;Ma et al, 2019;Wang et al, 2020;Li et al, 2021;Han et al, 2021;Ma et al, 2022), this is also a suitable ET database for use in climate studies covering the full study area with a high spatial resolution and a long time period. Our main findings are summarized below.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we developed a 37-year monthly ET dataset with a 0.01° spatial resolution for the 415 TP using the newly developed MOD16-STM model coupled with soil information to investigate the spatial distribution and temporal trends of the ET on the TP. Although previous studies have been conducted on the ET climatology on the TP (Peng et al, 2016;Wang et al, 2018;Ma et al, 2019;Wang et al, 2020;Li et al, 2021;Han et al, 2021;Ma et al, 2022), this is also a suitable ET database for use in climate studies covering the full study area with a high spatial resolution and a long time period. Our main findings are summarized below.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al (2017) estimated TP's ET (PM-Song) using the improved Penman-Monteith method and meteorological and satellite remote sensing 375 data with a spatial resolution of 1 km during 2000-2010, and they concluded that the average annual ET on the TP was 350.3 mm/year. In addition to this, the 18 mean annual ET values on the TP estimated using existing multi-source ET products (PML-Zhang (Zhang et al, 2019b), EB-ET (Chen et., 2019(Chen et., , 2021, CR-Ma (Ma et al, 2019) ssp126 (Eyring et al, 2016), GLDAS-Noah (Rodell et al, 2004), GLASS (Liang et al, 2021), GLEAM-v3.5b (Miralles et al, 2011), andERAR-Land (Muñoz-Sabater et al, 2021)) and previous research results (MTE (Jung et 380 al., 2010), PM-Li (Li et al, 2014a), LPJ-Yin (Yin et al, 2013)) are listed in Table 3 and shown in Fig. 10.…”
Section: Temporal Variations In Et Across Tpmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the time scale used in the above-mentioned studies was much longer, indicating that the ET rate on the TP has been increasing rapidly in recent years. Han et al (2021) revealed that the increasing rate in the eastern part of the plateau was mainly between 2.5 and 7.5 mm yr À1…”
Section: Et Mainly Derives From E On the Tpmentioning
confidence: 99%